Jade Elliston - Thesis submitted in partial fulfilment of the degree of Doctor of Clinical Psychology (DClinPsych) - Elliston, J (2023)
Systematic Review of the Literature: Previous empirical research has suggested that traumatic experiences in childhood may be linked to the development of hallucinations via dissociative processes. The current review aimed to assess the extent and quality of evidence supporting this mechanism to establish greater specificity in the understanding of how traumatic experiences confer risk of later psychopathology. A systematic search was undertaken using PsycINFO, Web of Science, PubMed, Embase, Medline, Global Index Medicus and KoreaMed. Titles and abstracts were screened, with eligible articles reviewed in full. Nineteen papers were identified, referring to twenty independent studies of varied methodologies, including both clinical and non-clinical populations globally. Although findings supported the role of dissociation as a mediator, with emerging evidence of specific pathways between trauma, dissociation and hallucinations across modalities, evidence is currently limited by cross-sectional methodologies and poor control of confounding variables. Implications for clinical practice and future research are discussed.